2021
DOI: 10.22541/au.161518112.26081982/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unlocking the potential plant growth-promoting properties of chickpea (Cicer arietinum L.) seed endophytes bio-inoculants for improving the soil health and crop production

Abstract: Sustainable agronomic practices are tried all over the world to promote safe and eco-friendly crop production. Therefore, in the present study, the effect of seed endophytic bacteria and its consortia on soil biochemical property, soil nutrient, and yield of chickpea (Cicer arietinum L.) under field and pot conditions are investigated. Both the experimental results proved a significant increase in total soil organic carbon (OC), electric conductivity (EC), organic matter (OM), soil nutrient like available N, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Castro et al [15] found the possibility of using poultry manure to improve burnt soil and increase rye-grass yield. The application of seed endophytic microbial consortium as bio-fertilizer helps to increase soil health and soil biodiversity, improved chickpea yield, and reduce the use of chemical fertilizers that are harmful to the environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Castro et al [15] found the possibility of using poultry manure to improve burnt soil and increase rye-grass yield. The application of seed endophytic microbial consortium as bio-fertilizer helps to increase soil health and soil biodiversity, improved chickpea yield, and reduce the use of chemical fertilizers that are harmful to the environment [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Phosphate‐solubilizing bacteria (PSB) are essential components in soil P cycling (Mahdi et al, 2020; Mukherjee et al, 2021). The PSB is the vital driver of P transformation and dominates the composition of P fractions.…”
Section: Introductionmentioning
confidence: 99%